The sasquatch escape - Selfors, Suzanne; Santat, Dan (New York ; Boston : Little, Brown and Co., 2013)
Spending the summer in his grandfather's rundown town, ten-year-old Ben meets an adventurous local girl and together they learn that the town's veterinarian runs a secret hospital for imaginary creatures.
3-6.
630L
Q
4.2
Keywords: Imaginary creatures -- Fiction; Veterinarians -- Fiction; Veterinarians -- Fiction; Adventure and adventurers -- Fiction; Fantasy